The Impact of Constitutional Replacements on the Quality of Democracy in Latin America - Strauka, Orestas (Politologija, 2020)
The article aims to evaluate whether and how constitutional replacements influence the quality of democracy in Latin American countries. The fuzzy-set qualitative comparative analysis method is applied while analysing 18 Latin American countries. The objective of the article- nine new constitutions that are assigned to the new constitutionalism period. The results reveal that constitutional replacements are neither sufficient nor necessary condition for quality of democracy. On the contrary, the parsimonious solution shows that quality of democracy can be explained by both high levels of education and inversion of constitutional replacements and inversion of constitutional replacements, institutionalised party system and non-homogeneous society. Inversion of quality of democracy analysis indicated that constitutional replacements, together with other conditions, form sufficient conditions for inversion of quality of democracy.
Keywords: Constitutional replacement; Latin America; Quality of Democracy; Fuzzy-set Qualitative Comparative Analysis; New Constitutionalism